1999
DOI: 10.1111/j.1651-2227.1999.tb00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year follow‐up of children born before 29 gestational weeks: health, cognitive development, behaviour and school achievement

Abstract: Stjernqvist K, Svenningsen NW. Ten-year follow-up of children born before 29 gestational weeks: health, cognitive development, behaviour and school achievement. Acta Paediatr 1999; 88: 557-62. Stockholm. ISSN 0803-5253 Since the mid-1990s several studies have reported poor school performance in extremely preterm infants. The necessity to provide a full picture of the child's situation has been indicated. In a southern Swedish population 32 120 infants were born during the 2-y period 1985-1986. In total, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
1
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(96 citation statements)
references
References 19 publications
9
78
1
8
Order By: Relevance
“…In the literature there is a continuing discussion about whether to use corrected or chronological age when comparing the results of preterm children with test norms or with the results of controls. Stjernqvist and Svenningsen (1999) suggested the use of corrected age at four years for ELBW children. Rickards et al (1989) suggested that a correction up to 8 1 ⁄ 2 years is reasonable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature there is a continuing discussion about whether to use corrected or chronological age when comparing the results of preterm children with test norms or with the results of controls. Stjernqvist and Svenningsen (1999) suggested the use of corrected age at four years for ELBW children. Rickards et al (1989) suggested that a correction up to 8 1 ⁄ 2 years is reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…There are no other Swedish population-based studies that are directly comparable to this one. Stjernqvist and Svenningsen (1999) made a 10-year follow-up in the mid-1990s but their study focused on extremely preterm children born before 29 weeks' of gestation. They also used another version of the Wechsler scales, the school age version (WISC-III) of the WPPSI-R scale and based the test results on chronological age, which makes comparisons difficult.…”
Section: Discussionmentioning
confidence: 99%
“…This dramatic practice can provoke anxiety and create a new family crisis (Sylvest 2000). Often, the health visitor 1 and general practitioner 2 assigned to the family do not have sufficient knowledge or training in caring for premature infants and their well-being and development, nor do they understand well enough the range of problems that could arise in this respect (Cusson & Lee 1993;Stjernquist & Svenningsen 1999).…”
Section: Frame Of Referencementioning
confidence: 99%
“…Potential extrapolations can be drawn that pertain to human auditory development. Several studies of long-term outcomes in NICU graduates cite speech and language problems (Stjernqvist and Svenningsen, 1999; Marlow et al, 2005; Kern and Gayraud, 2007). However, few studies have specifically linked them with noise type and levels.…”
Section: Relevance For Humansmentioning
confidence: 99%